Tumor-Derived Apoptotic Vesicles: With Death They Do Part - Muhsin-Sharafaldine, Morad-Remy; McLellan, Alexander D. (Frontiers in Immunology, 2018)
Tumor cells release lipid particles known as extracellular vesicles (EV) that contribute to cancer metastasis, to the immune response, and to thrombosis. When tumors are exposed to radiation or chemotherapy, apoptotic vesicles (ApoVs) are released in abundance as the plasma membrane delaminates from the cytoskeleton. Recent studies have suggested that ApoVs are distinct from the EVs released from living cells, such as exosomes or microvesicles. Depending on their treatment conditions, tumor-released ApoV have been suggested to either enhance or suppress anti-cancer immunity. In addition, tumor-derived ApoV possess procoagulant activity that could increase the thrombotic state in cancer patients undergoing chemotherapy or radiotherapy. Since ApoVs are one of the least appreciated type of EVs, we focus in this review on the distinctive characterization of tumor ApoVs and their proposed mechanistic effects on cancer immunity, coagulation, and metastasis.